Citogenotoxicidade e mutagenicidade da água do Sistema Estuarino de Santos-São Vicente - Cardoso, Caroline Margonato [UNIFESP] (2019)
The Santos-São Vicente Estuarine System (SESS) is one of the most degraded estuaries in Brazil. The disorderly urbanization of the Baixada Santista Metropolitan Region (RMBS) added with the inefficiency of regulatory mechanisms and basic sanitation, poverty, poor housing conditions, and environmental pollution make this region suitable for environmental monitoring studies. Thus, the aim of this study was to evaluate the water-induced cytogenotoxicity and mutagenicity of SSES collected at the points described as most contaminated (São Vicente and Piaçaguera Channels) using Wistar rats as an experimental model and Centropomus undecimalis fish. For this purpose, surface water was collected São Vicente Channel (SVC) and Piaçaguera Channel (PIC) of SESS and non-essential metals and metalloids (Cd, Pb, Hg and As) were quantified. Adult male Wistar rats were divided into four groups (n = 5) and exposed for 5 days: a) negative control received filtered water, b) saline control received saline water, c) experimental group received estuarine water from PIC and d) experimental group received estuarine water from SVC. Blood and liver were used for comet assay; bone marrow was used to perform the micronucleus test; histopathological, immunohistochemical analyzes (TNF-α, ki67 and 8-OHdG) and realtime PCR of caspase-3 were performed in the liver. The results revealed that rats exposed to water from SESS showed biological responses associated with genotoxicity, mutagenicity and cytotoxicity. Juvenile fish (n = 6) from C. undecimalis were collected from the SVC and compared to fish (n = 10) obtained from a pisciculture laboratory (control group). Micronucleus tests and nuclear abnormalities were performed with blood, and quantification of lipid peroxidation and DNA damage were performed with gills and livers of fish. Erythrocyte nuclear abnormalities in blood and lipid peroxidation in gills were higher in fish from SESS. In conclusion, SESS is capable of both mutagenic and cytotoxic activities in murine and fish, both having similar responses to environmental contaminants.